Despair, Hope, And Politics: A Semiotic Analysis Of Online Media Cartoons On The Turkey And Syria Earthquake 2023 - Sheikh, Dr. Adnan Rashid; Khan, Shaukat; Sultan, Dr. Ameer (Migration Letters, 2024)
The Turkey and Syria earthquake of 2023 caused widespread devastation and loss of life, resulting in widespread despair and hopelessness among the people. In the aftermath of the disaster, social media was flooded with caricatures that sought to represent the political and social realities of the affected regions. This research paper presents a semiotic analysis of online media cartoons using the Barthesian modal to understand the representation of despair, hope, and politics in the context of the Turkey and Syria earthquake of 2023. Through a qualitative analysis of purposively sampled cartoons, this study explores how dominant emotions and political messages are conveyed through visual and textual elements and how they shape public perception of the event. The findings suggest that the cartoons use a range of semiotic modalities, such as images, text, and symbolic representations, to convey political messages about the earthquake and its aftermath. The paper contributes to the growing research on semiotics and visual communication. It highlights the potential of online cartoons as a rich source of social and political insights in the context of the earthquake and how people respond to it.